Comment nous cherchons : l'utilité de la théorie de l'enquête deweyenne en formation d'adultes - Samuel Renier; Catherine Guillaumin (Université de Provence, 2017)
This paper relies on a close association of the study of John Dewey's thought and an empirical research on adult learning. It endeavors to relate the experience of a Master's course in Educational sciences, intended for adults continuing their education and students, in which the presentation of the research process has deliberately been based on John Dewey's theory of inquiry. One particular session is particularly analyzed out of this process, in order to understand how a reading of Dewey may represent a genuine pedagogical resource to help students elaborating their own research process. This study thus presents a twofold aim, insofar as it both questions the possibility of founding a pedagogical and epistemological process out of Dewey's logical theory, and the epistemological foundations of researches in Education in which experience is considered as the source and the end of the process.